Impediments to Proper Handling of Biomedical Waste in the Tertiary Health Facilities of Ekiti State, Southwest Nigeria (African Journal of Biomedical Research, 2024)
This study examined owners-based exogenous factors that could hamper adequate management and treatment of Biomedical Waste (BMW) at the Federal and State governments owned tertiary health facilities located in Ekiti State, Nigeria. Failure to address these impediments has been identified as bane of inadequate BMW management, capable of escalating insurgence of epidemics. The study employed survey research design using a well-structured five-item based questionnaire to elicit primary data from 103 purposively selected health officers from the two healthcare facilities. Evidence from relative importance index and One-way Contingency Chi-Square tests unveil that the five factors examined possess latency to impede adequate BMW management, but more for lack of modern medical waste management equipment and less for the health workers salary and allowances while the factors are found to be statistically significant in obstructing proper management of biomedical waste. The study concludes that failure to ensure that these factors are put in place can lead to inappropriate handling of medical waste which in turn can worsen disease outbreak in the environment. Thus, as a proactive measure to curb epidemics, it is recommended that government and hospital management boards should provide adequate fund to support this course in line with global best practices